Improving Students’ Learning Outcomes And Memory In Citizenship Learning With The Role Playing Learning Model - Primadani, Amelia (International Journal of Students Education, 2024)
This study aims to determine the improvement of learning outcomes and students’ memory through the application of the Role Playing learning model. Education is very important for students, with education students are able to master knowledge and skills that will be useful in society. Then the second is to see how effective this Role Playing Learning Model is when applied in teaching and learning activities. The data sources in this study come from journals with appropriate research topics and have been published. The author searches for articles contained in online journals and searches through Google Scholar. The author took 13 appropriate journals and analyzed them to describe the core of the selected literature in order to conclude whether the Role Playing method is able to improve students’ learning outcomes and memory or not. The research method used in this article is a systematic literature review, where the author traces published articles related to the title or topic of research that the researcher has determined. The author has traced 13 articles and it can be seen that this Role Playing Learning Model can improve learning outcomes and students’ memory.